Clarifying Muddied Waters, Part 1: A Secure Timeline for the James Leininger Case - Matlock, James G. (Journal of Scientific Exploration, 2022)
Drawing on dated emails and unpublished materials unavailable to Michael Sudduth, this paper establishes a secure, detailed timeline for the James Leininger reincarnation case. This secure timeline invalidates the timeline used by Sudduth in his critique of the case, while validating that of the Leininger family and investigator Jim Tucker. Links are provided to PDFs of supporting documents posted to the Psi Open Data repository.